Extraction of coconut oil from fresh-dry grated coconut meat using a hand-operated plate press - Magsalay, Maria Fedelis G. (1995)
A hand-operated plate press was used to extract the oil from fresh-dry grated coconut meat. The performance of the press was evaluated on its extraction efficiency and the quality of oil produced. Fouir factors were considered to affect its performance namely; pressure, moisture content, temperature and pressing time. however, only pressure, moisture content and temperature showed a significant interaction effect on the extraction efficiency. An optimum extraction efficiency of 61.1 % (based on available oil) was attained at 9-10% moisture content, at a pressure of 1035 KPa and a temperature range at 28-35°C. Press performance is lower when the optimum levels are not met. The quality of oil produced is water-white in color with a maximum of 0.1% free fatty acid (as lauric) content. An empirical equation was developed to predict the performance of the hand press as affected by the factors considered.
Computer print-out.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Coconut oil -- Philippines; Extraction (Chemistry).